Peran Organizational Citizenship Behavior Sebagai Upaya Optimalisasi Kinerja Pegawai Berbasis Work-Life Balance - Fadil Gema Imani; Adya Hermawati; Bambang Budiantono (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
The purpose of this study was to determine the effect of work-life balance on employee performance mediated by organizational citizenship behavior. The population in this study were all employee at Technical Unit of Vocational Training Wonojati in Malang. The sampling technique in this study used "Non Probability Sampling", and the sampling method in this study was Saturated Sample (Total Sampling) or Census. Respondents in this study were 32 people of that become an active employee at Technical Unit of Vocational Training Wonojati in Malang. The Data is processed through the software Smart-Partial Least Square 3 (Smart-PLS 3).The results showed that work-life balance has no significant effect on employee performance, work-life balance has a significant effect on organizational citizenship behavior, organizational citizenship behavior has a significant effect on employee performance. Organizational citizenship behavior acts as a mediator on the effect of work-life balance on employee performance at Technical Unit of Vocational Training Wonojati in Malang.